GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 10121 species occurrences available in GBIF matching the query: TaxonKey: Chenopodium hybridum L. HasGeospatialIssue: false HasCoordinate: true. The dataset includes 10121 records from 95 constituent datasets: 11 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 20 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 581 records from Botanical Society of the British Isles - Vascular Plants Database. 2 records from Phanerogamic Botanical Collections (S). 1 records from University of Vienna, Institute for Botany - Herbarium WU. 2 records from Herbarium Vonderau - FULD. 1 records from Naturalis Biodiversity Center (NL) - Botany. 9 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 14 records from FLORIVON. 11 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 141 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 1 records from BioFokus. 1 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 953 records from Artdata. 1 records from MBM - Herbário do Museu Botânico Municipal. 80 records from OHN. 25 records from Données ONF Faune-Flore-Fonge. 24 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 2 records from Herbier de Strasbourg. 4 records from Vascular Plant Herbarium, UiB. 9 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 1 records from iNaturalist Research-grade Observations. 1 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 16 records from CONN. 1 records from Collection botanique Le Grand A. (BOUM). 6 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 1 records from Herbarium Rhoenmuseum Fladungen. 1 records from Estonian University of Life Sciences. 1070 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 53 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 37 records from naturgucker. 1 records from MfN - Fossil plants (Cenophytic). 46 records from Dutch Vegetation Database (LVD). 3544 records from INPN - Données flore des CBN agrégées par la FCBN. 3 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 14 records from Tiroler Landesmuseum Ferdinandeum. 100 records from IBF Monitoring of Vascular Plants. 1 records from Tropicos Specimen Data. 10 records from Natural History Museum (London) Collection Specimens. 8 records from Natural History Museum, Vienna - Herbarium W. 15 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 2 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 1 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 2 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 2 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 3 records from Herbario de la Universidad de Almeria. 2 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 1 records from CIBIO, Alicante:ABH-GBIF. 1 records from Institut Botanic de Barcelona, BC. 6 records from Herbarium of Jyväskylä University Museum. 1 records from GEO Biodiversity Day. 7 records from Herbarium Berolinense. 1358 records from Observations du Conservatoire botanique national du Bassin parisien.. 35 records from Biologiezentrum Linz. 1 records from USU-UTC Specimen Database. 1 records from Institut Botanic de Barcelona, BC-Histórico. 395 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 2 records from Harvard University Herbaria. 2 records from Vascular plants of south-central China. 4 records from inatura - Erlebnis Naturschau Dornbirn. 11 records from Biodiversitätsdatenbank des Landes Salzburg. 1 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 2 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 1 records from Herbarium of Umeå University (UME). 32 records from Field Museum of Natural History (Botany) Seed Plant Collection. 25 records from Belgian IFBL Flora Checklists (1939-1971). 228 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 47 records from Biological and palaeontological collection and observation data MNHNL. 33 records from Botany Division, Yale Peabody Museum. 10 records from Herbarium Senckenbergianum (FR). 2 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 3 records from Vascular Herbarium, NMBU. 139 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 1 records from Flora d'Andorra. 237 records from Lund Botanical Museum (LD). 43 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 6 records from Carnet en Ligne. 2 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2 records from All observations extracted from the Flora of Northumberland and Durham 1831. 3 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 6 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 3 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 7 records from Vascular Plant Herbarium, Trondheim (TRH). 25 records from Données ONF Faune-Flore-FOnge. 18 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 13 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 416 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 55 records from Vascular Plant Herbarium, Oslo (O). 67 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 11 records from Nijmegen Natural History Museum (NL) - Herbarium. 1 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 20 records from Atlas des plantes vasculaires de Lorraine. 1 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups.
Keywords: GBIF; biodiversity; species occurrences